Comparison between Horn-Schunck and Brox techniques for Motion Detection in Thermal Video - Ramli, S.; Othman, N.; Zainudin, N.; Wahab, N. S. A.; Hasbullah, N. A.; Zizi, T. Tan; Azizi, F. Mohd; Ibrahim, N. (2016 International Conference on Information and Communication Technology (ICICTM), 2016)
The Motion Detection From The Thermal Video Using Optical Flow Technique was created to study motion detection techniques from thermal video using optical flow. The purpose of this application is to identify which techniques is more effective in detecting motion in thermal videos and to some extent it can drive technological development in the context of image processing. This application is developed to detect motion of an object in the distance occurred in the video. The program of the development Graphical User Interface (GUI) for this application is to facilitate users in order to use this application and to understand how these applications work. GUI is an intermediate medium between the user and a system. The technique developed for this application is called the Horn-Schunck and Brox technique. The analysed scene involved a video recording of a human dynamic motion. The analysis was done through an algorithm to detect motion based on the differences of the flow direction of the magnitude that occurs between image frames. The result of the analysis showed which one of the techniques is more effective in detecting the motion of objects that occurs in the video.